Subsistence Harvest of Salmon from Glennallen Subdistrict, Alaska, 1988-2016 - Alaska Department of Fish and Game, Division of Subsistence (Knowledge Network for Biocomplexity, 2018)
Subsistence fishing is important for the economies and cultures of many families and communities in Alaska. Subsistence uses of wild resources exist alongside other important uses of fish and game in Alaska and are especially important for many rural families who depend on subsistence use for nutrition and traditional cultural practices. Subsistence use is defined as the noncommercial, customary harvest and processing of wild resources for food, raw materials, and other traditional uses. These customs have been a central part of the traditions of many cultural and tribal groups in Alaska for centuries. Today, subsistence and personal use fisheries are open only to Alaska residents that have been living in the state for at least one year. The Board of Fisheries (BOF) has the authority to adopt regulations governing the use of fish resources in Alaska. In order to regulate subsistence fisheries and ensure sustainability, the BOF is directed by Alaskan state law to identify fish stocks that are customarily and traditionally used for subsistence in Alaska. After customary and traditional use has been determined for a stock, the amount reasonably necessary for subsistence is set. Subsistence and personal use fisheries are managed under different regulations and thus regulations vary by fishery and location across the state. For example, only some fisheries require a permit issued by ADFG and some waters are closed to subsistence fishing, other fisheries have season, gear, and/or bag limit restrictions. Finfish other than salmon, rainbow trout, and steelhead trout may be taken for subsistence purposes at any time in any area of the state by any method unless restricted by the subsistence fishing regulations in the Alaska Admin Code. Salmon are more strictly regulated and the fisheries require permits, only allow certain gear types, and are restricted to certain waters in the state. This dataset includes information on subsistence salmon harvest from 1988-2016 in the Glennallen Subdistrict of Alaska. This dataset includes information on the amount of harvest by community and year, additionally broken down by species and the type of gear used. The csv file "Glennallen_Harvest.csv" has been reformatted from the original file ("Glennallen District By Gear and Permit - All Years.csv"). This processing was done using the R Markdown file, "Glennallen_Subsistence.Rmd", which moves the file from wide to long format, and creates some simple plots.